EFFECT OF FINANCIAL PERFORMANCE ON PROFIT GROWTH IN PT. SEMEN TONASA (PERSERO) IN PANKEP REGENCY - Wairooy, Muhamad Ali (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This study aims to test and analyze the effect of financial performance on profit growth at PT. Semen Tonasa (Persero) in Pangkep Regency. Data collection using secondary data using samples in this study is a saturated sample (census). The population in this study is the number of years of financial performance (ROA) and the number of years of profit growth at PT. Semen Tonasa (Persero) in Pangkep Regency, which is 36 months from 2015 - 2017, while the sample taken is the number of observations for 36 months (January 2015-December 2017). The data obtained were analyzed using simple linear regression analysis, t test and test coefficient of determination (R²) which processing was carried out with SPSS version 23. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. This means that financial performance has a positive and significant effect on earnings growth.